The Effect of Liquidity, Sales Growth, and Company Size on Capital Structure (Case Study on Transportation Companies Listed on the Indonesian Stock Exchange) - Sinta Devi Firanti; Wulan Suryandani (Universitas Islam Lamongan, 2023)
The capital structure of the business is its long-term debt and equity funding. In this study, the capital structure of transportation businesses listed on the Indonesian Stock Exchange (IDX) from 2013 to 2021 was tested and the impact of liquidity, sales growth, and company size was determined. There are 43 transportation businesses listed on the Indonesian Stock Exchange, but only 5 of them are utilized as examples because they have complied with the requirements. Purposive sampling was the sampling strategy utilized. The method for documenting research data is the data gathering method. Multiple linear regression analysis is the technique used for data analysis. The findings revealed that the capital structure is significantly impacted negatively by liquidity, significantly positively by sales growth, and hardly impacted positively by firm size. The adjusted R2 value obtained from the coefficient of determination test is 0.409, which means that the variation in the three independent variables CR, SG, and S can account for 40.9% of the variation in capital structure, with other factors other than those included in the study's model accounting for the remaining 59.1% of the variation